KARAKTERISASI DAN ADSORPSI KARBON TERSULFONASI DARI BAMBU ANDONG DENGAN PERBEDAAN UKURAN PARTIKEL - Lisna Efiyant; Angelica Paramasari; Poedji Hastoeti; Dadang Setiawan; Novitri Hastuti; Nela Rahmati Sari; Ani Iryani (Jurnal Penelitian Hasil Hutan, 2022)
Carbon has many benefits as an adsorbent, catalyst, drug delivery, energy, and it can produced from various resources, includinglignocellulosic biomass. One of the potential biomass for carbon material is bamboo. The particle size is usually inversely proportionalto the surface area and adsorption level; therefore, studying the particle size of activated carbon is essential. This research aims toproduce carbon and sulfonated carbon from andong bamboo to understand the effect of particle size on the characteristics andadsorption capacity. The method for this research was the pyrolysis of andong bamboo into sulfonated carbon bioproducts usingH2SO4 10N with variations in particle size of 60 and 100 mesh. The proximate analysis of activated carbon based on IndonesianNational Standard (SNI) No.06-3730-1995 includes moisture content, ash content, volatile matter content, and fixed carbon.Sulfonated carbon adsorption analysis was conducted on iodine, methylene blue, ammonia, chloroform, and benzene compounds.The result showed that the proximate parameters of activated carbon produced had met the SNI requirements. The adsorptioncapacity of activated carbon on the adsorption of iodine, methylene blue, ammonia, chloroform, and benzene was 421.71432.50mg/g; 20.3521.90 mg/g; 9.559.98 mmol/g; 10.1615.03%, and 4.63.83%, respectively. Based on andong sulfonatedcarbon data, it can be used as an adsorbent and renewable green catalyst.